(untitled) (Bangladesh Medical Journal, 2014)
The terms free flap and free tissue transfer are synonymous used to describe the movement of tissue from one site on the body to another. "Free" implies that the tissue, along with its blood supply, is detached from the original location (donor site) and then transferred to another location (recipient site). However, studies are still going on about the different aspects of its success and failure. The present case report is one such step to share our experience. In this case report successful microvascular free tissue transfer was possible With the increase in experience we can expect increased success rate as well. DOI: http://dx.doi.org/10.3329/bmj.v40i2.18515 Bangladesh Medical Journal 2011 Vol.40(2): 62-64